ON FREE VIBRATION OF A NONHOMOGENEOUS ORTHOTROPIC RECTANGULAR PLATE ON A NONHOMOGENEOUS VISCO-ELASTIC FOUNDATION - VAGIF OGLY HACIYEV; GULNAR ROVSHAN MIRZAYEVA; AZIZ INTIZAR SHIRIEV (Structural Mechanics of Engineering Constructions and Buildings, 2017)
In the paper, by using approximate analytic methods, the study a problem of vibrations of a nonhomogeneous rectilinear plate and a visco - elastic foundation, the boundary conditions are homogeneous. It is assumed that the modules of elasticity and density of the plate are characteristic functions of three space coordinates, the Poisson ratios are accepted to be constant [1]. The numerical calculation is carried out under specific values of characteristic functions, characterizing the properties of the plate and foundation, and the results are represented in the form of tables and dependence graphs